Dynamics of Judges' Considerations in The Determination Of Marriage Dispensation at The Enrekang Religion Court - Alam, Nur Alam (IAIN Parepare, 2022)
The main study in this thesis is the dynamics of judges' considerations in determining the dispensation of marriage at the Enrekang Religious Court. Ideally, marriages are carried out in accordance with existing regulations, but there are still opportunities provided by the state for prospective brides and families/guardians of prospective brides who still wish to enter into underage marriages. Data at the Religious Court of Enrekang every year there has been an increase in marriage dispensation cases being handled in the last 4 years. In 2017, 35 cases were received, in 2018, 36 cases were received, but in 2019 there was a spike in cases as many as 42 cases, this was as a result of the enactment of Law no. 16 of 2019 and in 2020 as of July 10 2020 there have been 70 cases that have been submitted. This type of research is field researchqualitative research methods through normative juridical and sociological juridical approaches.The paradigm of this research is constructivist. Data sourceprimary is the determination of marriage dispensation andthe testimony of the judges, while secondary data comes from scientific books, accredited journals, theses, dissertations and documents related to the object of research. The research instruments are observation guidelines, interview guidelines and documentation tools.Data collection techniques areobservation, in-depth interviews and documentation. Data processing techniquesby describing it in the form of sentences that are orderly, coherent, logical, not overlapping and effectivewhile data analysis includes:data checking, classification, verification, data analysis, conclusion. As for tthe technique of testing the validity of the data is using a triangulation technique. The results of the study showed that (1) the discrepancy between the applicant's expectations and the request for a marriage dispensation was not granted in accordance with the Marriage Dispensation Stipulation of the Enrekang Religious Court, indicating that there was a social conflict contained in the stipulation. And the applicant still marries her child with her future husband but is not registered at the Office of Religious Affairs or married in an unregistered manner which will have a social impact because there is no recognition from the state, problems in managing population administration and others. (2) The factors considered by the judge in determining the dispensation for marriage at the Enrekang Religious Court are psychological, health, educational and economic factors. (3). The dynamics in determining the marriage dispensation at the Enrekang Religious Court can be seen in the determination of the marriage dispensation, differ from one case to another. Because sometimes judges differ in giving legal considerations to a case. If there is a difference of opinion in an assembly, a vote is made on the case by following the majority vote after going through deliberation. After the entry into force of PERMA No. 5 of 2019 which regulates the settlement of marriage dispensation cases is a single judge, this will reduce the complexity in examining and determining marriage dispensation. This provision has been enforced at the Enrekang Religious Court since the date of its stipulation. If there is a difference of opinion in an assembly, voting will be carried out on the case by following the majority vote after going through deliberation. After the entry into force of PERMA No. 5 of 2019 which regulates the settlement of marriage dispensation cases is a single judge, this will reduce the complexity in examining and determining marriage dispensation. This provision has been enforced at the Enrekang Religious Court since the date of its stipulation. If there is a difference of opinion in an assembly, voting will be carried out on the case by following the majority vote after going through deliberation. After the entry into force of PERMA No. 5 of 2019 which regulates the settlement of marriage dispensation cases is a single judge, this will reduce the complexity in examining and determining marriage dispensation. This provision has been enforced at the Enrekang Religious Court since the date of its stipulation.